2011
DOI: 10.1002/cncr.26480
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in cancer screening in individuals with a family history of breast or colorectal cancer

Abstract: Background Understanding racial/ethnic disparities in cancer screening by family history risk could identify critical opportunities for patient and provider interventions tailored to specific racial/ethnic groups. We evaluated whether breast cancer (BC) and colorectal cancer (CRC) disparities varied by family history risk using a large, multiethnic population-based survey. Methods Using the 2005 California Health Interview Survey, BC and CRC screening were evaluated separately with weighted multivariate regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…Access to a physician and having a physician recommend screenings are important predictors of screening behavior [8,9,12,13,22]. Due to age and insurance laws in Hawaii, our population most likely had access to health care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to a physician and having a physician recommend screenings are important predictors of screening behavior [8,9,12,13,22]. Due to age and insurance laws in Hawaii, our population most likely had access to health care.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between ethnicity and these factors have emerged as areas of interest [13,2225]. The purpose of the current study was to examine how ethnicity and other factors influence colonoscopy, PSA, and mammography screening among participants of the Multiethnic Cohort (MEC).…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have identifi ed low breast cancer screening uptake in underserved women, 22,23 a populationbased study of individuals with a family history of breast cancer found no signifi cant racial/ethnic or income disparities in uptake of breast cancer screening. 24 It is possible that the strong family histories of breast cancer in our survey population made these women and their health care providers especially attentive to breast cancer screen- Odds ratios less than 1.0 indicate variables independently associated with decreased self-reported general health.…”
Section: Discussionmentioning
confidence: 97%
“…For diverse populations, our findings document racial/ethnic and social gaps in access to and use of PM diagnostics. One reason may be because a perception of one's family history risk may vary by race/ethnicity (Ponce et al 2012). On the supply side, PM diagnostics, such as GEP to inform use of adjuvant chemotherapy for early-stage breast cancer, have not been adequately validated in minority populations (Odierna et al 2011).…”
Section: Diffusion Of Personalized Medicinementioning
confidence: 99%